2022
DOI: 10.1017/dmp.2022.47
|View full text |Cite
|
Sign up to set email alerts
|

Role of Community Health Volunteers Since the 2015 Nepal Earthquakes: A Qualitative Study

Abstract: Objective: Nepal female community health volunteers (FCHVs) were the first available health personnel in communities during the 2015 Nepal earthquakes. This study explored the facilitating factors and barriers of the FCHVs during health emergencies. Methods: In-depth interviews with 24 FCHVs and 4 health managers from 2 districts in Nepal (Gorkha and Sindhupalchowk) were conducted using semi-structured interview guides. The qualitative data were analyzed using thematic analysis methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Overall, our findings suggest that financial compensation is crucial for women volunteers—who mostly come from a poor socioeconomic background—to be motivated to deliver global goals for PHC [ 6 , 21 , 54 , 57 , 58 ]. As highlighted in earlier studies of FCHVs, Nepal needs a system that not only socially recognises volunteers’ efforts, but also supports their livelihood: it is only when both these are met that volunteers will be able to deliver their role with the support of family members [ 46 , 62 , 63 ]. This however, has financial implications for achieving health related goals (SDG3), suggesting that more financial investment for FCHVs is needed for integrated action across three levels (individual, organisational and community).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings suggest that financial compensation is crucial for women volunteers—who mostly come from a poor socioeconomic background—to be motivated to deliver global goals for PHC [ 6 , 21 , 54 , 57 , 58 ]. As highlighted in earlier studies of FCHVs, Nepal needs a system that not only socially recognises volunteers’ efforts, but also supports their livelihood: it is only when both these are met that volunteers will be able to deliver their role with the support of family members [ 46 , 62 , 63 ]. This however, has financial implications for achieving health related goals (SDG3), suggesting that more financial investment for FCHVs is needed for integrated action across three levels (individual, organisational and community).…”
Section: Discussionmentioning
confidence: 99%
“…These combined sources were subsequently analyzed to create preliminary recommendation statements for the next phase of the study. [24][25][26][27][28] This paper reports the final part of the overall Health EDRM workforce development project: the Delphi consensus study. The focus of this consensus study was to identify strategic recommendations for strengthening the workforce for Health EDRM in lowand middle-income countries (LMIC) and high-income countries (HIC).…”
Section: Health Edrm Workforce Development Research Projectmentioning
confidence: 99%
“…In a study exploring health-care volunteers' experiences during the 2015 Nepal earthquake, financial incentives provided by governments and/or professional bodies would support their households during their absence and they were able to continue working in peace. 30 Other studies also indicate that volunteer health-care team members, when motivated by incentives, are able to continue delivering services without experiencing any financial restraints or debt concerns. [31][32][33] Findings reported that a few participants who had previous experience in volunteering services during disasters felt more confident in providing services and quickly adapted to the new role.…”
mentioning
confidence: 99%